Internalisasi Nilai – Nilai Agama Islam Guna Meningkatkan Harmoni Masyarakat Melalui Majelis Selawat - Imami, Agus Sultoni; Najiburahman, Moh Farhan (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to explore the role of majelis selawat in the process of internalizing Islamic values and its impact on social harmony. As a form of collective worship, majelis selawat not only strengthens the spiritual relationship with Allah but also serves as a social space that strengthens relationships among community members. The process of internalizing Islamic values in this study is based on sociopsychological theory, which examines how social and psychological environments influence the behavior of individuals and groups. This research uses a qualitative approach with a case study method on a community that regularly holds majelis selawat. Data were collected through in-depth interviews, participatory observation, and documentation to understand the transformation of Islamic values in social life. The results of the study show that majelis selawat plays an important role in instilling values of love, peace, and mutual respect, thereby strengthening ukhuwah islamiyah and a sense of togetherness. The internalization of these values impacts the creation of social harmony, reduction of conflict potential, and an increase in community solidarity. Thus, majelis selawat has great potential as an effective means of building a harmonious society through the continuous internalization of Islamic values at various social levels.